The Translational Fabric of Mission and Culture: Engaging Cross-Cultural Theologies on Translation - Hintersteiner, Norbert (Interreligious Studies and Intercultural Theology, 2019)
Within theological circles Robert J. Schreiter stands out for his extensive culture theory and theology engagement. Interestingly, therein, the area of cultural translation has not figured prominently in his scholarship, despite having enjoyed a certain pride of place at the times of his early career, both in mission studies and in cultural semiotics, his favorite theory of culture. What is suggested here then is to review the missional discourse of cross-cultural translation (Andrew Walls, Lamin Sanneh and Kwame Bediako), on the one hand, and its critiques from contextual theology (Stephan Bevans and Robert Schreiter) on the other, explaining his reservation. Additionally, the essay elaborates on translation in cultural semiotics (Yuri Lotman) and recent translation studies with its foundational as well as fluid concept of translation, not dissimilar to Schreiter’s understanding of globalized culture, suggesting it as potential terrain for future theologies of crosscultural translation.